Mental Illness and Prison Reentry in a High Risk Context - Barrenger, Stacey (2013)
Reentry programs for persons with serious mental illness (SMI) leaving jails or prisons have produced mixed results (Chandler & Spicer, 2006), including those for evidence-based treatments (EBT). These interventions occur in the complex nexus of the mental health and criminal justice systems and the effects of the intervention can be facilitated or constrained by the environment in which they operate (Smith, Jennings, Cimino, 2010; Solomon and Draine, 1995; Weisman, Lamberti, & Price, 2004). This dissertation explores how the economic, social, physical, and political factors that comprise the risk environment interact with an EBT for persons with SMI and contribute to poor outcomes for this population. Utilizing a multi-informant, multi-perspective framework, in-depth interviews were conducted with 28 participants and 6 staff members involved in a randomized field trial testing the effectiveness of Critical Time Intervention (CTI) for men with mental illnesses leaving prison in New Jersey. Participants completed between one and five interviews (total, 38 interviews) in order to capture the different stages of reentry. Other data collection methods included observation through attending team meetings and conducting go-along interviews and document analysis through reviewing team meeting notes and client progress notes. The risk environment posed significant challenges for participants in acquiring basic needs, including income and housing, as punitive public and social policies excluded resources to individuals based on their criminal history. These policies played within an environment with multiple opportunities to engage in illegal activities under heightened criminal justice scrutiny, but few prosocial opportunities. Case managers were also challenged to provide resources under this context and relied on emotional support as a primary component of their work. A combination of individual, interpersonal, and environmental factors combined to produce risk for reincarceration and also impinged on the intervention possibly undermining its effectiveness. As EBTs are disseminated widely, adapted to different settings, and applied to new populations, there are more opportunities for their effectiveness to be undermined by the noise of real-world settings. The risk environment in certain high-risk communities needs to be addressed or else they little chance of improving the lives of those we seek to help